Una via filosofica e al femminile per il dialogo tra islam e cristianesimo - Lazzeri, Sabrina (Annali di studi religiosi, 2005)
This short paper presents the author’s research for her thesis in Religious Studies, dealing with the discovery of the possibility (regarding the dialogue with Islam) of drawing on two rich terrains that offer countless starting points for theological reflection: the philosophical terrain and the world of gender identity (the role of women as mediators and catalyzers of dialogue). The hypothesis of dialogue revolves around the thematic and existential nucleus of being different, a vast wealth to be discovered but, even more so, a mystery to be respected.